Facial Affect Manifested By Multiple Oscillations - Güntekin, Bahar; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
The present study describes electrophysiological differentiation of "Facial Expressions" by using the method of event-related oscillations (EROS). These measures were used to assess electrical manifestations of emotional expressions of 20 healthy subjects exposed to neutral, angry, and happy" faces. The present study extended previous analysis to frequency windows of delta (0.5-3.5 Hz) and theta (5-8.5 Hz) oscillations. No significant differences among responses to various face expression stimuli were observed, however, topological differences in response to all facial expressions were found. Delta oscillatory responses in the parietal-temporal-occipital locations were larger than the frontal and central locations, whereas theta oscillatory responses in the right temporal-occipital electrodes were larger than the right central electrodes. Assessment of topologically distributed multiple oscillations opens a new avenue for understanding of the electrophysiology of recognition of "faces" and "facial expressions". (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Face Recognition; Face Expressions; Emotion; Event Related Oscillations; Delta; Theta; Brain Oscillations; Visual Cortex; Face; Memory; Grandmother; Recognition; Expressions; Attention; Responses; Yüz Tanıma; Yüz İfadeleri; Duygu; Olaya İlişkin Salınımlar; Teta; Beyin Salınımlar; Görsel Korteks; Yüz; Bellek; Büyükanne; Tanıma; İfade; Dikkat; Tepkiler